The clinical implications of Porphyromonas gingivalis and its detection methods – a systematic review - Shalihin, Mohd Shaiful Ehsan; Suhaimi, Nur Aina Nabilah; Hamzah, Hairul Aini; Abidin, Sulhi; Aidid, Edre Mohammad; Musa, Ramli (Malaysian Medical Association (MMA), 2023)
Introduction: Mounting evidence has shown the significant correlation between periodontitis and the development of other comorbidities, such as cardiovascular disease due to periodontopathogenic bacterial migration and colonisation. As the main etiologic agent of periodontitis, the role of Porphyromonas gingivalis (P. gingivalis) has been widely explored as the main culprit and its early detection is crucial to control the exacerbation of diseases. This review aims to identify and summarise all clinical diseases that potentially developed due to the presence of P. gingivalis and discover all its detection methods that have been developed.